Verhaltensontogenese bei Hundewelpen der Rasse Samojede in den ersten acht Lebenswochen - Günther, Antje (Tierärztliche Hochschule, 2009)
This study analyses and documents the early behavioural ontogenesis of Samoyed puppies within the scope of an ethological comparison of breeds. An ethogram of the development of the Samoyeds´ first eight weeks of life forms the central theme of this study and is completed by notes about the mothers´ behaviour.The Samoyeds´ behavioural inventory is discussed in comparison with other domestic dog breeds and the European Wolf (Canis lupus lupus L.). Furthermore, the Samoyed´s pace of development is determined within the spectrum of breeds and selected aspects of the puppies´ behaviour are analysed quantitatively. The paper concludes by considering different popular science theses about the Samoyed from an ethological point of view. For this study, 19 Samoyed puppies from three litters, which were kept and bred under comparable familiar conditions in the homes and gardens of two different breeders, were monitored from birth until the 56th day of life with standardised methods. The developmental ethogram documents an almost complete behavioural catalogue of the Samoyed compared with the European Wolf. No relevant behavioural patterns or even complete behavioural domains are omitted. However a certain hypotrophy in the extent of agonistic behaviour is striking: Although aggressive behavioural traits are generally completely formed, the puppies solely use them in the context of social play, which never leads to serious aggressive conflicts. The contact between the puppies and the dams is also nearly free of aggression and aggressive behaviour of the Samoyeds towards human beings was never registered. Compared with wolf cubs the development of the Samoyed puppies takes a slightly accelerated course. Amongst the different breeds of domestic dogs, the Samoyeds´ pace of development in consideration of various aspects can clearly be determined in a middle position. It is however obvious that the development of the Samoyed is considerably retarded in comparison to the Siberian Husky, another nordic dog breed. At the age of ...